Development of IoT Learning Media for Hybrid Learning Using Wokwi Simulation - Anori, Sartika; Fikri, Ryan; Jalinus, Nizwardi; Ernawati, Ernawati; Fadhilah, Fadhilah (Universitas Negeri Padang, 2025)
The rapid development of Internet of Things (IoT) technology requires learning media that are able to support practical competencies in flexible learning environments. However, IoT learning implementation in hybrid learning faces major challenges related to limited laboratory facilities and hardware availability. This study aims to develop IoT learning media based on hybrid learning using Wokwi Simulation as a virtual laboratory solution. The research employed a Research and Development (R&D) approach using the 4D development model, consisting of define, design, develop, and disseminate stages. The feasibility of the developed media was evaluated through expert validation and practicality testing. Validation involved three subject matter experts and three media experts, analyzed using Aiken’s V coefficient. The results showed that the learning media achieved high validity, with an average Aiken’s V value of 0.846 from material experts and 0.929 from media experts. Practicality testing conducted with 15 students resulted in a practicality level of 91.33%, categorized as very practical. These findings indicate that the developed IoT learning media is valid, practical, and suitable for supporting hybrid learning. The integration of Wokwi Simulation provides flexible access, reduces dependency on physical hardware, and enhances students’ learning experiences in IoT practical activities.Keywords— IoT, Hybrid Learning, Learning Media, Wokwi Simulation, Virtual Laboratory.